Pengaruh Engagement terhadap Post Stroke Fatigue (PSF) dan Kemampuan Motorik Pasien Pasca Stroke Iskemik - Kurniawan, Hendri; Sutopo, Haris (Jurnal Terapi Wicara dan Bahasa, 2024)
Abstract Background: Rehabilitation efforts for post-stroke patients to restore motor skills often do not provide optimal results. This is allegedly related to the client's seriousness or involvement in undergoing therapy (neurorehabilitation). Post-stroke comorbid problems in the form of post-stroke fatigue (PSF) may also influence this. Objectives: The research aims to examine the effect of engagement on post stroke fatigue (PSF) and recovery of motor skills in ischemic stroke patients. Methods: Observational quantitative research with a cross sectional design. The study was conducted in a hospital occupational therapy unit. The sampling technique uses purposive sampling technique. The research instruments used include: engagement rating scale (ERS), fatigue severity scale (FSS) and Fulg-Meyer Assessment (FMA). Research data analysis uses descriptive analysis, correlative and regression tests using the SPSS version 20 program. Results: The majority of the research sample was male (67.5%), and onset < 24 months (75%).   Mean ERS score = 21.2 ± 0.38, mean FSS change score = 2.17 and mean Fugl-Meyer change score = 2.45. Correlative test of ERS with FSS (r=0.697; p=0.000) and ERS with Fugl-Meyer (r=0.462; p=0.003). The linear regression test shows that the determinant coefficients of 0.486 and 0.226 ERS on FSS and Fugl-Meyer are significant with the equations Y=19.179+0.929X and Y=19.755+0.590X. Conclusion: Engagement influences a decrease in fatigue by 48.6% and an increase in motor ability recovery by 22.6%. Keywords : stroke, engagement, fatigue, motor